La modernidad problemática - Ottone F., Ernesto (Estudios Internacionales, 1995)
This work is part of the effort to locate the reflection promoted by ECLAC since the 1990s with the proposal of productive transformation with equity in a broader context of the debate originated by the profound political-cultural changes that have accompanied the end of the Cold War and have especially put cultural particularities in tension with the universalist vocation of modernizing processes. To do this, it reviews the different analysis approaches of the new international scenarios, locates the centrality of the cultural dimension, and attempts to analyze the tensions and dynamisms between cultural identity and modernity, to conclude by outlining these challenges in our region.